2019
DOI: 10.1183/16000617.0066-2019
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter and the airway epithelium: the special case of the underground?

Abstract: Airborne particulate matter (PM) is a leading driver of premature mortality and cardiopulmonary morbidity, associated with exacerbations of asthma and chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis, and lung cancer. The airway epithelium, as the principal site of PM deposition, is critical to the effects of, and initial response to, PM. A key mechanism by which PM exerts its effects is the generation of reactive oxygen species (ROS), inducing antioxidant and inflammatory responses in expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 111 publications
0
45
0
Order By: Relevance
“…Furthermore, it has been observed that endotoxin contamination, a component of some environmental PM preparations, may cause an intracellular accumulation of cytokines, including IL-1β [44], although previous findings indicate that endotoxin is usually found on coarse PM [45]. To further investigate the inflammatory effects of the synthetic soot, future studies should also examine the expression of IL-8 and TNF-α, as these genes have been implicated in numerous human lung diseases [46,47] and found to be upregulated in human bronchial epithelial cells exposed to PM [48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been observed that endotoxin contamination, a component of some environmental PM preparations, may cause an intracellular accumulation of cytokines, including IL-1β [44], although previous findings indicate that endotoxin is usually found on coarse PM [45]. To further investigate the inflammatory effects of the synthetic soot, future studies should also examine the expression of IL-8 and TNF-α, as these genes have been implicated in numerous human lung diseases [46,47] and found to be upregulated in human bronchial epithelial cells exposed to PM [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that exposure to PM 2.5 induces a loss of SOD2 and CAT activity, leading to an accumulation of ROS [24]. PM 2.5 has also been observed to downregulate protein kinase B (Akt) signaling, which is a known modulator of SOD2 and NFE2L2, decreasing the expression of SOD2 and NFE2L2 [49,50]. Another study observed that NFE2L2 expression in human BEAS-2B bronchial epithelial cells is downregulated when cells are subjected to high concentrations of PM 2.5 or repeated exposure protocols [51].…”
Section: Discussionmentioning
confidence: 99%
“…17 Thus, the aim of this study was to characterise changes in the transcriptome of differentiated mucociliary cultures of PBECs following exposure to underground UFPM whose composition is unlike ambient PM, yet to which millions of people are regularly exposed, leading to potential health risks. 18 This study highlights a number of previously unobserved gene perturbations in response to UFPM, including novel observations of widespread and significant upregulation of metallothionein (MT) gene expression.…”
Section: Introductionmentioning
confidence: 93%
“…PM is associated with almost 9 million deaths per year worldwide. 103 Main sources are traffic, diesel and coal combustion, and industry. In just a few years, a substantial increase in forest fires in California, Amazon, and Australia has significantly increased the levels of PM exposure, and studies have demonstrated extreme levels of tissue damage due to smoke and PM especially in wildfires.…”
Section: Ozonementioning
confidence: 99%
“…105 According to aerodynamic diameter, PM is further categorized as coarse PM (PM with a diameter <10 mm, called PM 10 ) and fine PM (PM with the diameter <2.5 mm [PM 2.5 ]). 103 The composition, size, biological properties, and physical properties of particles are related to the changes in the region, season, and time. PM 2.5 mainly consists of heavy metals, carbon sources, sulfate, ammonium, nitrate, and various ions.…”
Section: Ozonementioning
confidence: 99%